PENGALAMAN KELUARGA MISKIN DALAM PEMENUHAN NUTRISI PADA BALITA DI LINGKUNGAN PELINDU, KELURAHAN KARANGREJO, KECAMATAN SUMBERSARI, JEMBER - Hanny Rasni (Fakultas Kesehatan Masyarakat, Universitas Jember, 2009)
Pelindu, Kelurahan Karangrejo, Kecamatan Sumbersari, Kabupaten Jember is an area with a large number of poor family but it has no record of the malnutrition case. This research aims to find out the meaning of poor family’s experience in fulfilling the children nutritient need. Applies with descriptive fenomenologic design, population is the poor family that has children under five years old. 6 mothers who give primary education to their children act as research informants that are selected by purposive sampling method and the analysis of the data uses Colaizzi method. The result shows that : 2 themes on the family’s respon toward the poverty: family valuation on their economic state and their household finance management pattern; the family behaviour in fulfilling nutrient for their children that can be classify in 3 themes : colostrum, Breastfeed Matur, formulaic milk, food giving; nutrient supplying method which consist of 3 themes: the access method of the family to nutrient sources, the principle of food supplying and the family health maintenance; the strenght and weakness of health care which consist of 3 themes: accepted health care intervention, the weakness and effectiveness of health care; the family expectation to the health care which consists of 2 themes: the improvement of service and health facility and also the infrastructure improvement. The nurse who works for the community and family has to consider the available resources, the value and belief hold by of those families especially within their cultural background. Keywords: poor family experience, the nutrient fulfillment and the children under five years old